Afrorreligiosos no ensino superior: trajetórias de escolarização de lideranças na região metropolitana de Vitória/ES - Krull, Maria Raquel Souza (2023)
The present study aimed to investigate the path of Afro-religious leaders in higher education, seeking to find out how they managed to integrate terreiro knowledge with academic knowledge and what contributions educational advancement provides to the holy people. To this end, it presents and discusses part of the results of the Umbanda temple mapping research carried out by the Transatlantic Africanities Project: history, culture and Afro-Brazilian memories at the Federal University of Espírito Santo (UFES). Thinking about Afro-religious culture and the educational field, we analyzed, in addition to other relevant aspects, the educational trajectories of religious leaders, babalorixás and ialorixás, understanding that religious racism has permeated these subjects throughout history, and within the school walls it is no different, That's why many followers silence their faith, deny their beliefs and have their culture erased from school planning. The data points to discriminatory actions, both in the territory of worship and in the environments of educational institutions. The work was developed through exploratory research in axé terreiros in the municipalities of Fundão, Serra, Vitória, Cariacica, Vila Velha, Viana and Guarapari. We dialogue with scholars who address religious racism within schools, we think about the orality of knowledge understood in terreiros and we use memory and life trajectories as an investigative method. We bring the support of legal frameworks, which advocate the representation of the cultural identity and traditions of traditional peoples and communities in formal education and higher education, thus ensuring that ethnic diversity is presented in its entirety, reaching beliefs, customs and religion of all subjects. We found that, in addition to the training process that leaders promote within the terreiros based on their traditional knowledge, the experiences and knowledge acquired in the academic and educational environment exert a significant influence on the social actions they carry out in their communities and are expanded in favor of the population. in general, breaking many stereotypes.